Reimagining the Role of Technology towards Innovative Pedagogies in Teaching and Learning - Harwati Hasyim (IAHN-TP Palangka Raya, 2022)
Emerging technologies such as Mixed Reality (MR), Augmented Reality (AR), Immersed Augmented Reality (IVR) and Artificial Intelligent (AI) are paving the way for the future of education. These new technologies are changing the education landscape. Since these technological trends in education are growing, there is a need to look at how these technologies could be integrated successfully into the learning ecosystem. To apprehend the benefits of technology in education and provide authentic learning experiences, educators need to use technology effectively in their teaching practices. Hence, it is vital to revisit the role of technology in providing meaningful teaching and learning experiences. This paper showcases emerging practices of technology integration in teaching and learning and how each technology plays an important role in the implementation of innovative pedagogies. Additionally, the key lessons learnt from the emerging practices and the way forward are also shared. As a suggestion, more research should be conducted in investigating the impacts of these emerging technologies in teaching and learning.